Investigating the Determinants of the Street Code and its Relation to Offending among Adults - Piquero, Alex R. (American journal of criminal justice, 2012)
Theoretical and empirical consideration has long been given to the role of subcultural attitudes and how they relate to delinquency and crime. Recently, Anderson has reconceptualized these early attitudinal depictions by considering the formation and role of these specific attitudes or ‘code of the street’ among African-Americans in inner-city neighborhoods. A number of important findings have emerged from this literature, yet much remains to be considered. We contribute to this literature in three specific ways by examining: (1) the scope of street code attitudes across a wide variety of individuals—and not just inner-city African American (males) to assess the generalizability of these attitudes; (2) the correlates of street code attitudes; and (3) the extent to which street code attitudes mediate the relationship between various demographic and attitudinal (self-control) variables and crime. Theoretical implications and directions for future research are addressed.